2003
DOI: 10.1105/tpc.016246
|View full text |Cite
|
Sign up to set email alerts
|

A Class-V Myosin Required for Mating, Hyphal Growth, and Pathogenicity in the Dimorphic Plant PathogenUstilago maydis [W]

Abstract: In the early stages of plant infection, yeast-like haploid sporidia of Ustilago maydis respond to pheromone secreted by compatible partners by forming conjugation tubes. These then fuse to generate a dikaryotic hypha that forms appressoria to penetrate the host plant. As a first step toward understanding the structural requirements for these transitions, we have identified myo5 , which encodes a class-V myosin. Analysis of conditional and null mutants revealed that Myo5 plays nonessential roles in cytokinesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 64 publications
7
109
0
Order By: Relevance
“…In agreement with some role of Pcl12 in the formation of the conjugation tubes, we found that pcl12 was induced after pheromone treatment ( Figure 7C). These data suggest that Pcl12 plays a role in the polar growth of the conjugation tube, although we cannot exclude some indirect effect such as the possibility that Pcl12 participate in pheromone sensing as it has been recently proposed for Myo5 and Yup1 (Weber et al, 2003;Fuchs et al, 2006). To address this issue, we took advantage of the fuz7DD allele, which encodes an activated version of the mitogenactivated protein kinase (MAPK) kinase involved in pheromone response (Banuett and Herskowitz, 1994;Mü ller et al, 2003), since cells expressing this allele under the arabinose-induced crg1 (D) Pcl12-induced filamentation is dependent on cdk5.…”
Section: Absence Of Pcl12 Delays the Formation Of The Conjugation Tubementioning
confidence: 90%
See 2 more Smart Citations
“…In agreement with some role of Pcl12 in the formation of the conjugation tubes, we found that pcl12 was induced after pheromone treatment ( Figure 7C). These data suggest that Pcl12 plays a role in the polar growth of the conjugation tube, although we cannot exclude some indirect effect such as the possibility that Pcl12 participate in pheromone sensing as it has been recently proposed for Myo5 and Yup1 (Weber et al, 2003;Fuchs et al, 2006). To address this issue, we took advantage of the fuz7DD allele, which encodes an activated version of the mitogenactivated protein kinase (MAPK) kinase involved in pheromone response (Banuett and Herskowitz, 1994;Mü ller et al, 2003), since cells expressing this allele under the arabinose-induced crg1 (D) Pcl12-induced filamentation is dependent on cdk5.…”
Section: Absence Of Pcl12 Delays the Formation Of The Conjugation Tubementioning
confidence: 90%
“…To distinguish between these possibilities, we introduced a fusion protein of GFP and Myo5, a class V myosin from U. maydis that is transported via actin cables toward the growing end of the cell (Weber et al, 2003). GFP-Myo5 signal appeared at the filament tip in control and mutant cells ( Figure 3C), indicating that the ability to detect and direct transport toward the hyphal tip was not impaired.…”
Section: Pcl12 Mutants Are Unable To Focalize the Growth In The Filammentioning
confidence: 99%
See 1 more Smart Citation
“…Potential proteins that need to be localised by mRNA transport in U. maydis include enzymes involved in cell wall synthesis, such as chitin synthases (Weber et al, 2003), components of the endocytosis machinery (Steinberg et al, 2001), regulatory proteins such as small G proteins (Mahlert et al, 2006), or cell-shape determinants such as septins (Boyce et al, 2005). The latter example is of particular interest, because septins were initially identified to function during septation in S. cerevisiae (Gladfelter, 2006) and localise at the hyphal tip as well as the distal septum in filaments of Candida albicans (Warenda and Konopka, 2002).…”
Section: Rrm4 Is Probably Involved In Rna Transportmentioning
confidence: 99%
“…For construction of pRIYC1, genomic FB2 DNA was amplified with primers RG1/RG2 (59-CATGCCATGGAAAA-GATTCGCCCCACATTG-39/59-GAGCTCATGAAACGCTTTCGTCTCCA-CCTTC-39). PCR products were digested with NcoI/BspHI and inserted into the NcoI site of plasmid p123-YFP, which enables YFP expression under the otef promoter (Weber et al, 2003). For construction of pRAGC1, genomic FB2 DNA was amplified with primers RG1/RG3 (59-GAGCTCATGAGACGAGGTGCGTCAGC-39).…”
Section: Fusion Constructsmentioning
confidence: 99%